2012
DOI: 10.1093/cid/cis936
|View full text |Cite
|
Sign up to set email alerts
|

Candida glabrata Sepsis Associated With Chorioamnionitis in an In Vitro Fertilization Pregnancy: Case Report and Review

Abstract: We report a case of Candida glabrata sepsis associated with chorioamnionitis in an in vitro fertilization-assisted pregnancy. There is a strong association between C. glabrata chorioamnionitis and assisted fertility techniques. Candida glabrata chorioamnionitis presents unique management challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…However, it actually has reduced virulence and migration ability across intact chorionic membranes as compared to Candida albicans . This may explain why the majority of the only 20 reported cases of C. glabrata chorioamnionitis in the literature [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19] involved some form of instrumentation and were associated with IVF [5,6,7,8,9,10,16,17,18,19] or presence of an intrauterine device [11,12,20,21]. …”
Section: Resultsmentioning
confidence: 99%
“…However, it actually has reduced virulence and migration ability across intact chorionic membranes as compared to Candida albicans . This may explain why the majority of the only 20 reported cases of C. glabrata chorioamnionitis in the literature [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19] involved some form of instrumentation and were associated with IVF [5,6,7,8,9,10,16,17,18,19] or presence of an intrauterine device [11,12,20,21]. …”
Section: Resultsmentioning
confidence: 99%
“…glabrata infection has also been reported as a cause of chorioamnionitis in healthy pregnant women [6][7][8]. The majority of cases appear to be reported in the IVF population and present at 15-24 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cases appear to be reported in the IVF population and present at 15-24 weeks gestation. The authors propose that the possible source of infection is the lower genital tract, with introduction of organisms into the uterus at time of embryo transfer [6][7][8]. In the non-IVF population, C. glabrata chorioamnionitis has been associated with foreign bodies (cerclage and intrauterine devices) and immunosuppression (untreated gestational diabetes) [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C glabrata 's lack of pseudohypha formation results in decreased tissue adherence and difficulty in invading intact membranes9; hence many of its associated risk factors are those which permit direct introduction of the fungus into the endometrial cavity. Predisposing risk factors include antibiotic therapy, immunosuppression, underlying medical conditions, such as diabetes mellitus, coexisting intrauterine device, IVF-embryo transfer (ET), cervical stitch, rupture of membranes, and amniocentesis or chorionic villous sampling 3 4 13. A review of 16 cases of C glabrata chorioamnionitis in 2012 revealed that 63% of the cases were associated with IVF, and 81% with some form of instrumentation 3.…”
Section: Discussionmentioning
confidence: 99%